The quality of service in the public health sector: an empirical investigation - Valenzuela F., Leslier (Estudios de Administración, 2008)
This article evaluates the value perceived by the user of the Center of Primary Health in study versus the value delivered by this organization with the purpose to determine the gap in the quality of the service and the factors that affect. There has used the model SERVQUAL already validated for the sector health. The results indicate that the value of the gap is negative since the polled users were waiting for a better service of what actually they received or perceived. The most important dimensions in the study to evaluate the quality of the service were Security and Tangibility.